Workload Manageability Among Novice Special and General Educators: Relationships With Emotional Exhaustion and Career Intentions. (July 2017) - Bettini, Elizabeth; Jones, Nathan; Brownell, Mary; Conroy, Maureen; Park, Yujeong; Leite, Walter; Crockett, Jean; Benedict, Amber
Novice special educators (those in their first 3 years) consistently report their workloads are unmanageable. Yet, it is not clear whether their perceptions of workload manageability contribute to outcomes of concern such as emotional exhaustion (a component of burnout) or intentions to continue teaching in their schools and districts. This pilot investigation used structural equation modeling to analyze data collected for the Michigan Indiana Early Career Teacher Study. We found (a) novice elementary and middle school special educators rated their workloads less manageable than novice elementary and middle school general educators; (b) novice special and general educators' ratings of workload manageability predicted emotional exhaustion, which mediated a relationship between workload manageability and career intentions; and (c) the magnitude of the relationships was stronger for novice general educators. Results have implications for supporting and retaining novice special and general education teachers.